An exploratory qualitative study of menstrual hygiene management among adult women of reproductive ages from an under-resourced community in Cape Town, South Africa - Ncube, Semkelisiwe (Department of Public Health and Family Medicine, 2024)
Background: Poor menstrual hygiene management can result in health concerns for women, particularly in low-and-middle-income countries. The evidence for the lived menstruation experiences of adult women of reproductive ages is limited. This study sought to understand the menstrual hygiene management experiences of adult women from an under-resourced community in Cape Town in South Africa. Methods: In this exploratory qualitative research design, qualitative in-depth interviews were conducted using a semi-structured interview guide with 10 women aged 25 and 49 and three key informants namely a maternal health nurse and two community health care workers. The study occurred over a period of three months and all participants were purposively selected using a homogenous sampling strategy and key informants were purposively sampled using an intensive sampling strategy. Data was manually analysed using Braune & Clarke (2016) thematic data analysis and coding was done deductively and inductively to look for emergent codes. Findings were organized around a conceptual framework developed to map the distal and proximal factors affecting girls and women menstrual hygiene management in LMICs. Results: Women menstrual experiences were shaped by their socio-cultural context and resource limitations. The main findings include psychological impacts of poor menstrual hygiene management namely shame, discomfort, culminating in feelings of powerlessness, loss of confidence, increased anxiety, and negative perceptions of menstruation. Physical health challenges related to compromised menstrual hygiene including skin irritation and rashes, increased risk of reproductive tract infections. Financial challenges culminating in poor access to and use of pain relief medication and use of substandard sanitary materials. Poor menstrual hygiene management also led to environmental pollution caused by disposal of sanitary materials and in day-to-day activities, poor menstrual hygiene led to avoidance of sexual activities and public places, reduced performance, and participation at work. Conclusion: Adult women from an under-resourced community in Cape Town experience poor menstrual hygiene management affecting their physical and psychological health. Recommendations: There is need for health education about menstruation, improved access to resources and health services required for proper MHM and further research and programming among adult populations.